Utility-based Physical Appraisal of Eucalyptus Hybrid Plantations in India Under the Risk of Illicit Felling - Trivedi, S. N. (Indian Forester, 1989)
This paper discusses three models to incoporate the risk of illicit felling and applies them to predict the yield from Eucalyptus hybrid plantations in India for a spacing of 2 m Ã— 2 m. The optimum rotations for different quality classes are discussed. The paper shows that losses concentrated by area are more serious than those removing the same proportion of cumulative volume with or without affecting the increment.